2007
DOI: 10.1002/art.23071
|View full text |Cite
|
Sign up to set email alerts
|

Effect of meniscal damage on the development of frequent knee pain, aching, or stiffness

Abstract: Objective. To evaluate the effect of meniscal damage on the development of frequent knee pain, aching, or stiffness in middle-aged and older adults.Methods. The Multicenter Osteoarthritis Study is a prospective study of 3,026 individuals 50 years of age or older who have or are at high risk of developing knee osteoarthritis (OA). We investigated knees at baseline and at 15 months. Case knees (n ‫؍‬ 110) were those with no pain, aching, or stiffness on most days at baseline, but that had developed frequent pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
88
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(93 citation statements)
references
References 31 publications
2
88
0
3
Order By: Relevance
“…2,[31][32][33] For example, one study showed no significant association between the presence of meniscal damage and the development of frequent knee pain in middle-aged and older adults, once the co-occurrence of osteoarthritis at baseline was taken into account. 34 Previous cohort studies have suggested that progression of osteoarthritis may be more rapid in persons who have undergone arthroscopic partial meniscectomy 35,36 ; it is uncertain whether this is an effect of the surgery. 37 Longterm follow-up of patients in the present trial and in other trials 8,38 is needed to address this question.…”
Section: Discussionmentioning
confidence: 99%
“…2,[31][32][33] For example, one study showed no significant association between the presence of meniscal damage and the development of frequent knee pain in middle-aged and older adults, once the co-occurrence of osteoarthritis at baseline was taken into account. 34 Previous cohort studies have suggested that progression of osteoarthritis may be more rapid in persons who have undergone arthroscopic partial meniscectomy 35,36 ; it is uncertain whether this is an effect of the surgery. 37 Longterm follow-up of patients in the present trial and in other trials 8,38 is needed to address this question.…”
Section: Discussionmentioning
confidence: 99%
“…Tears in this age group usually result from long-term degeneration of the meniscus itself and cause joint swelling, joint line pain and mechanical locking. [8][9][10] The presence of meniscal tears has been identified as an important risk factor in the development of knee osteoarthritis. 10,11 Degenerative meniscal tears are associated with articular cartilage defects, loss of articular cartilage volume and prevalence of radiographical osteoarthritis.…”
Section: Fundingmentioning
confidence: 99%
“…The feasibility of the DEA implementation was established using data from the NIH/NIAfunded Multicenter Osteoarthritis (MOST) study (Englund et al, 2007). The MOST study used a population-based sampling frame to recruit 3026 community-dwelling men and women, age 50-79 years, with frequent knee symptoms (progression cohort) or at risk for developing symptomatic knee OA, based on a history of knee injury, surgery, or being overweight/obese (incidence cohort).…”
Section: Feasibility Of Dea Implementation Established In Epidemiologmentioning
confidence: 99%
“…For the most part, however, these studies have involved lengthy and concerted efforts in well-controlled research settings, and have yielded articular contact stresses for only small numbers of cases. The high logistical cost of performing 3-D contact FEA on a subject-or patient-specific basis makes FEA of limited attraction for stress analysis in large epidemiologic studies (Englund et al, 2007;Felson & Nevitt, 2004;Lester, 2008). Advancement of expeditious methods for determining in vivo articular contact stress distributions will enhance the understanding of normal articular function, and of the mechano-pathology of OA.…”
mentioning
confidence: 99%